Blended Finance - Flammer, Caroline,Giroux, Thomas,Heal, Geoffrey (National Bureau of Economic Research, 2024)
Blended finance—the use of public and philanthropic funding to crowd in private capital—is a potential way to finance a more sustainable world. While blended finance holds the promise of being catalytic in mobilizing vast amounts of private capital, little is known about this practice. In this paper, we provide a conceptual framework that formalizes the decision-making of development finance institutions (DFIs) that engage in blended finance. We then provide empirical evidence on blended finance using data from a major DFI. The key variable we study is the level of concessionality, which captures the subsidy from the blended co-investment. Our findings indicate that DFIs provide higher concessionality for projects that have a higher sustainability impact per dollar invested. Moreover, the concessionality is higher for projects in countries with higher political risk and a higher degree of information asymmetries. In such cases, the blending tends to also include risk-management provisions. These findings are consistent with the predictions from our conceptual framework, in which DFIs have a limited budget that they allocate across projects to create societal value
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Entwicklungsfinanzierung; Agrarkredit; Entwicklungsorganisation; Sustainable Development Goals; Welt; Non-bank Financial Institutions; Financial Instruments; Institutional Investors; Public Goods; Economic Development; Sustainable Development; Agricultural Finance